Creating emotional resonance: Interpersonal emotion work and motivational framing in a transgender community - Schrock, Douglas; Holden, Daphne; Reid, Lori (Social Problems, 2004)
In this article, we examine how interpersonal emotion work in a transgender support group and motivational framing of transgender social movement organizations together constructed favorable conditions for emotional resonance. We define emotional resonance as the emotional harmony and/or disjuncture between collective action frames and the emotional lives of potential recruits. Data derive from fieldwork, interviews, online e-mail lists and forums, community publications, activist speeches, and social movement organizations' recruitment appeals. Transgendered people joined support groups hoping to find relief from shame, fear, powerlessness, alienation, and inauthenticity. Although group members' emotion work partly accomplished such relief, it was hindered by identity conflicts and the temporal bounds of the meetings. Transgender activists and nascent social movement organizations, however, used motivational framing to promise targeted recruits a more permanent emotional resolution—one which could draw them into the movement. Our analysis moves transgender scholarship beyond issues of identity and moves framing theory beyond an almost exclusive concern with cognitive processes.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; care; identités LGBTQIA2+; militance; mouvements sociaux; personnes trans*; périodes historiques; ressource en ligne; régions géographiques; thématiques; émotions; états-unis